Utilization of cardiac resynchronization therapy in patients with heart failure in the Northern Region of New Zealand. Issue 1 (2nd November 2018) - Looi, Khang‐Li; Gavin, Andrew; Sidhu, Karishma; Cooper, Lisa; Dawson, Liane; Slipper, Debbie; Lever, Nigel
Abstract: Background: Cardiac resynchronization therapy (CRT) has been shown to improve morbidity and mortality for heart failure (HF) patients. Little is known about the trends in CRT use and outcomes of these patients in New Zealand. Method: Mortality, hospitalization events and complications in HF patients in the Northern Region of New Zealand implanted with CRT devices from Jan‐2007 to June‐2015 were reviewed. Results: Two‐hundred patients underwent CRT implantation during the study period. There was a gradual increase in CRT‐D implantation (n = 157) but the number remained static for CRT‐P (n = 43). Patients who received CRT‐P were older (mean age 65.9 ± 14.0 years vs 61.5 ± 10.2 years, P < 0.0007) but had a higher left ventricular ejection fraction (LVEF) (33.7 ± 10.5% vs 24.7 ± 6.1%, P < 0.0001) than those undergoing CRT‐D implant procedures. During a median follow‐up of 4 (2.8) years, 29 (14.5%) patients (14.7% in CRT‐D vs 13.9% in CRT‐P, P = 0.91) had died. HF was the cause of death in 73.9% of the patients. There was no difference in all‐cause mortality between patients with CRT‐D and CRT‐P. Conclusions: Despite the proven benefits of CRT in selected HF patients, there continued to be under‐utilization of these devices in HF patients in the Northern Region. Reasons for under‐utilization of these devices need further exploration. These data should be useful for benchmarking individual patient management and national practice against wider experience in the country.